Abandoned project through the medium of unfavourable economic condition in Malaysia - Danial Adib, Kamaruddin (2019)
Abandoned of housing projects during construction is a prevailing problem that the housing sector in Malaysia has been experiencing since 1980s. This paper aims to highlight the causes and impacts of economic growth towards the abandoned housing projects. Factors pertaining to projects abandonment can be categorized into economic, financial, legal, managerial, system-related, and unforeseen risks. The study reveals main impacts of abandoned housing projects which is economic impacts. For this purpose, the study will look into how the extent of the impact of rising raw material prices, labor wage prices and transport machinery prices especially in Peninsular Malaysia towards the growth of number in abandoned housing project.